Development of a mobile-based cognitive development monitoring application for early detection of stunting with an extreme programming approach - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
The global health problem of stunting was the focus of the research, aiming to provide innovative and personalized solutions to parents or guardians in maintaining their children's health. The XP method was used in the app development to ensure efficient planning, high code quality, and quick response to changes. Test results of the app features included nutritional intake monitoring, reminder notifications, healthy food guidance, and a supportive community forum. The user acceptance evaluation showed a more than 85% satisfaction rate, indicating that the app successfully met user expectations. The contribution of this research lies in providing an effective tool for stunting prevention, accurate information, community support, and a satisfying user experience. As such, this research positively contributes to global efforts to improve children's health and reduce the prevalence of stunting.